Regulation of disease signaling by YOD1: potential implications for therapeutic strategies - Jiawei Zhao; Xiaotong Guo; Houzhong Li; Yujing Chen; Jingjing Du; Juzheng Zhang; Jinfeng Gan; Peitao Wu; Siqi Chen; Xinwen Zhang; Jinfeng Yang; Jiamin Jin (Cancer Cell International)
Abstract YOD1 (OTUD2) is a pivotal deubiquitinating enzyme (DUB) of the Otubain family. It plays an essential role in protein degradation and the regulation of cell signal transduction, influencing various biological processes. The activity of YOD1 is mediated through its three structural domains: the Ubiquitin Regulatory X (UBX) domain, the Zinc Finger (ZNF) domain, and the Ovarian Tumor (OTU) domain. Specifically, the UBX domain regulates protein interactions, mitochondrial quality control, and immune responses. The ZNF domain facilitates protein localization, degradation, and cancer progression. The OTU domain drives deubiquitination, ensuring protein stability and regulating key signaling pathways. In recent years, increasing attention has been paid to the role of YOD1 in various diseases. Studies have demonstrated that YOD1 influences critical cellular activities such as proliferation, apoptosis, migration, and invasion by modulating key signaling pathways, including Hippo and TGF-β. Abnormal YOD1 expression is closely linked to the development of several cancers, including breast, liver, and lung cancer. Moreover, in non-malignant conditions such as inflammation and vascular diseases, YOD1 plays a key role in maintaining tissue homeostasis and repairing damaged tissues. Given its multifaceted roles in both tumorigenic and non-tumorigenic contexts, YOD1 is considered a promising target for therapeutic strategies. This review systematically analyzes the key signaling pathways regulated by YOD1, with a focus on elucidating its potential therapeutic value in cancer and various non-tumor diseases. Additionally, it provides a comprehensive review of the recent research progress in the field of YOD1 inhibitors. Our aim is to underscore the significance of YOD1 as a potential therapeutic target, to provide a theoretical basis for the development of innovative therapeutic strategies, and to offer new perspectives and insights for future related research.